Leaf anatomy, inclination, and gas exchange relationships in evergreen sclerophyllous and drought semideciduous shrub species - Gratani, L; Bombelli, A (PHOTOSYNTHETICA, 1999)
There are significant differences in leaf life-span among evergreen sclerophyllous species and drought semideciduous species growing in the Mediterranean maquis. Cistus incanus, which has a leaf life-span of four-eight months, was characterised by the highest net photosynthetic rates (PN). while Quercus ilex and Phillyrea latifolia, which maintain their leaves two-three and two-four years, respectively, had a lower PN- The longer leaf life-span of the two evergreen sclerophyllous species may be justified to cover the high production costs of leaf protective structures such as cuticle, hairs, and sclereids: cuticle and hairs screen radiation penetrating into the more sensitive tissues, and sclereids have a light-guiding function. Q. ilex and P. latifolia have the highest leaf mass/area ratio (LMA = 209 g m(-2)) and a mesophyll leaf density (2065 cells per mm(2) of leaf cross section area) about two times higher than C. incanus. In the typical evergreen sclerophyllous species the steepest leaf inclination (alpha = 56 degrees) reduces 42% of radiation absorption, resulting in a reduced physiological stress at leaf level, particularly in summer. C. incanus, because of its low leaf life-span, requires a lower leaf investment in leaf protective structures. It exhibits a drastic reduction of winter leaves just before summer drought, replacing them with smaller folded leaves. The lower leaf inclination (alpha = 44 degrees) and the lower LMA (119 g m(-2)) of C. incanus complement photosynthetic performance. Water use efficiency (WUE) showed the same trend in Q. ilex, P. latifolia, and C. incanus, decreasing 60% from spring to summer, due to the combined effects of decreased CO2 uptake and increased transpirational water loss.
Keywords: cistus incanus; leaf inclination; leaf life-span; leaf mass/area ratio; leaf thickness; net photosynthetic rate; phillyrea latifolia; Quercus ilex; transpiration rate